Magnetization transfer saturation reveals subclinical optic nerve injury in pediatric-onset multiple sclerosis. (February 2023) - Longoni, Giulia; Martinez Chavez, Edgar; Young, Kimberly; Brown, Robert A; Bells, Sonya; Fetco, Dumitru; Kim, Laura; Grover, Stephanie A; Costello, Fiona; Reginald, Arun; Bar-Or, Amit; Marrie, Ruth Ann; et al.
Background: The presence of subclinical optic nerve (ON) injury in youth living with pediatric-onset MS has not been fully elucidated. Magnetization transfer saturation (MTsat) is an advanced magnetic resonance imaging (MRI) parameter sensitive to myelin density and microstructural integrity, which can be applied to the study of the ON. Objective: The objective of this study was to investigate the presence of subclinical ON abnormalities in pediatric-onset MS by means of magnetization transfer saturation and evaluate their association with other structural and functional parameters of visual pathway integrity. Methods: Eleven youth living with pediatric-onset MS (ylPOMS) and no previous history of optic neuritis and 18 controls underwent standardized brain MRI, optical coherence tomography (OCT), Magnetoencephalography (MEG)-Visual Evoked Potentials (VEPs), and visual battery. Data were analyzed with mixed effect models. Results: While ON volume, OCT parameters, occipital MEG-VEPs outcomes, and visual function did not differ significantly between ylPOMS and controls, ylPOMS had lower MTsat in the supratentorial normal appearing white matter (−0.26 nU, p  = 0.0023), and in both in the ON (−0.62 nU, p  < 0.001) and in the normal appearing white matter of the optic radiation (−0.56 nU, p  = 0.00071), with these being positively correlated (+0.57 nU, p  = 0.00037). Conclusions: Subclinical microstructural injury affects the ON of ylPOMS. This may appear as MTsat changes before being detectable by other currently available testing.